Jasmonic acid-dependent and -independent signaling pathways control wound-induced gene activation in Arabidopsis thaliana. - Titarenko, E (1997)
Plant response to mechanical injury includes gene activation both at the wound site and systemically in nondamaged tissues. The model developed for the wound-induced activation of the proteinase inhibitor II (Pin2) gene in potato (Solanum tuberosum) and tomato (Lycopersicon esculentum) establishes the involvement of the plant hormones abscisic acid and jasmonic acid (JA) as key components of the wound signal transduction pathway. To assess in Arabidopsis thaliana the role of these plant hormones in regulating wound-induced gene expression, we isolated wound- and JA-inducible genes by the differential mRNA display technique. Their patterns of expression upon mechanical wounding and hormonal treatments revealed differences in the spatial distribution of the transcripts and in the responsiveness of the analyzed genes to abscisic acid and JA. A correlation can be established between sensitivity to JA and the accumulation of the transcripts in systemic tissues upon wounding. A comparative study of the wound response in wild-type and JA-insensitive coi1 mutant plants indicated that in A. thaliana wound signals are transmitted via at least two different pathways. One of them does not involve JA as a mediator and is preferentially responsible for gene activation in the vicinity of the wound site, whereas the other requires JA perception and activates gene expression throughout the aerial part of the plant.